2024
DOI: 10.3389/fimmu.2024.1342210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenoprotein extracts from Cardamine hupingshanensis on growth, selenium metabolism, antioxidant capacity, immunity and intestinal health in largemouth bass Micropterus salmoides

Hao Zhang,
Long Zhao,
Penghui Zhang
et al.

Abstract: This study aimed to assess the impact of dietary selenoprotein extracts from Cardamine hupingshanensis (SePCH) on the growth, hematological parameters, selenium metabolism, immune responses, antioxidant capacities, inflammatory reactions and intestinal barrier functions in juvenile largemouth bass (Micropterus salmoides). The base diet was supplemented with four different concentrations of SePCH: 0.00, 0.30, 0.60 and 1.20 g/Kg (actual selenium contents: 0.37, 0.59, 0.84 and 1.30 mg/kg). These concentrations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
2
2
0
Order By: Relevance
“…Furthermore, the expression levels of Cu/Zn-SOD, Mn-SOD, GPX1b, and GR were higher in the TS and GTS groups than in the PS and GPS groups, suggesting that TS and GTS may be more effective at improving antioxidant status in largemouth bass. Moreover, our results also found higher Nrf2 levels and lower Keap1b levels were mainly shown in the PS group and the GPS group compared to the GLU group, respectively, consistent with previous findings in fish species with better antioxidant capability [32,47]. Given the pivotal roles of Nrf2/Keap1 in initiating the expression of antioxidant enzymes, it demonstrated that adequate polysaccharide sources could contribute to maintaining redox homeostasis and improve antioxidant capability in largemouth bass.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the expression levels of Cu/Zn-SOD, Mn-SOD, GPX1b, and GR were higher in the TS and GTS groups than in the PS and GPS groups, suggesting that TS and GTS may be more effective at improving antioxidant status in largemouth bass. Moreover, our results also found higher Nrf2 levels and lower Keap1b levels were mainly shown in the PS group and the GPS group compared to the GLU group, respectively, consistent with previous findings in fish species with better antioxidant capability [32,47]. Given the pivotal roles of Nrf2/Keap1 in initiating the expression of antioxidant enzymes, it demonstrated that adequate polysaccharide sources could contribute to maintaining redox homeostasis and improve antioxidant capability in largemouth bass.…”
Section: Discussionsupporting
confidence: 91%
“…In order to alleviate the potential oxidative stress and maintain redox homeostasis, aerobic organisms have evolved numerous antioxidant enzymes, including SOD, CAT, GSS, GPX, and GR, etc. [32,46]. In this study, we observed markedly elevated levels of Cu/Zn-SOD, Mn-SOD, and GPX1b in the four starch groups compared to the GLU group.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is well known that ROS are always produced during the metabolic process of various extrinsic nutrients, which could impact activities of antioxidant enzymes or functional proteins, including SOD, GST, CAT, GR, GPX, etc. [ 83 ]. Previous studies have found that the antioxidant capacities were reduced in large yellow croaker fed SO diets when compared with FO diets [ 82 ].…”
Section: Discussionmentioning
confidence: 99%